An update on the clinical use of drug-coated balloons in percutaneous coronary interventions. (2nd June 2016) - Cheng, Yanping; Leon, Martin B.; Granada, Juan F.
ABSTRACT: Introduction : Drug-coated balloons (DCB) promise to deliver anti-proliferative drugs and prevent restenosis leaving nothing behind. Although, randomized clinical trials have demonstrated their efficacy for the treatment of in-stent restenosis, clinical evidence supporting their use in other coronary applications is still lacking. Areas Covered : This review summarizes the development status of clinically available DCB technologies and provides an update on the current data for their coronary use. Expert Opinion : Current generation DCB prevent restenosis by delivering paclitaxel particles on the surface of the vessel wall. Although clinically available technologies share a common mechanism of action, important differences in pharmacokinetic behavior and safety profiles do exist. Future technological improvements include the development of coatings displaying: high transfer efficiency; low particle embolization potential; and alternative drug formulations. Optimized balloon-based delivery systems and drug encapsulation technologies also promise to improve the technical limitations of current generation DCB. Although proving clinical superiority against DES may prove to be difficult in mainstream applications (i.e., de novo ), new generation DCB technologies have the potential to achieve a strong position in the interventional field in clinical settings in which the efficacy of DES use is not proven or justified (i.e., bifurcations).